Optimalisasi Waktu Fiksasi Menggunakan Formalin 10% Pada Ginjal, Hepar, dan Pankreas Tikus Sprague Dawley Untuk Pewarnaan Haematoxylin-Eosin - Alwi, Muhammad Azharan; Rachmawati, Nurlaely Mida; Ariany, Devy; Hermawati, Luluk; Zulfa, Hilizza Awalina (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2025)
Background: Histotechnology is a series of procedures used to prepare histological specimens for microscopic analysis. One of the critical steps in this process is fixation, which serves to preserve tissue structure and prevent changes in shape or size. However, excessive fixation duration may lead to over-hardening of tissues, resulting in reduced quality of histological observations. Objectives: To evaluate the feasibility of two week formalin 10% fixation period on histological quality of kidney, liver, and pancreas tissues. Methods: After a 14-day adaptation period, male Sprague Dawley rats were anesthetized, necropsied, and their kidney, liver, and pancreas were fixed in 10% formalin. Histotechnical procedures included graded alcohol dehydration, toluene clearing, paraffin embedding, 6 µm sectioning, and HE staining. Preparations were observed using an Olympus BX41 microscope at magnifications of 4x–40x. Results: Two-week fixation caused structural damage to the kidney, liver, and pancreas. Damage observed included glomeruli and tubules in the kidney, the portal triad structure in the liver, and the Langerhans islet cells in the pancreas. Statistical results (if any) should be included here. Conclusions: Fixation for two weeks did not produce adequate histological preparations, and therefore, it is not recommended as a reference for developing histotechnology SOPs in related laboratories.